Travestis, o gênero inventado: um confronto com o estado da arte - Silva Neto, Manuel Vaz (2014)
This thesis seeks to understand the process by which the transvestites enter the discourses of gender as elements of social exclusion. Ie, this Thesis is to seek the most fundamental meaning of this supposed exclusion held by disciplinary power. Demand, of course, question the foundational bases under which the transvestites appear in your reality genre as well, resize your entire oppositional political character. Thus, transvestites are not presented as individuals who touched the disciplinary power merely delete them for reasons of irregularity rules, but to bring it to the place where they have always been: to his statement. So do not play that character overdue, humiliated and excluded as common in the group of transvestites individual research on this thesis. I searched through solid arguments demonstrate the strong and independent constitutive character transvestite, ie, sought to demonstrate that the basis of gender was less of transvestites seated under revolucinarias, insurrectionary, contesting political bases. As will be seen, its foundational character finds in his will to dominate.